Optimal measuring timing of cystatin C for early detection of contrast-induced acute kidney injury: A systematic review and meta-analysis. (January 2020) - Chen, Chu-Ting; Chang, Ling-Yin; Chuang, Ching-Wei; Wang, Shih-Ching; Kao, Ming-Chang; Tzeng, I-Shiang; Kuo, Ko-Lin; Wu, Chin-Chieh; Tsai, Pei-Shan; Huang, Chun-Jen
Highlights: Cystatin C (CysC) is a superior biomarker to serum creatinine for early detection of contrast-induced acute kidney injury (CIAKI). The optimal CysC measuring timing for early detecting CIAKI is at 24 h after contrast agent exposure. Positive findings on the diagnostic accuracy of CysC for early detecting CIAKI can be made based on absolute CysC values or increased magnitudes from baseline. Abstract: Objective: The optimal measuring timing of serum/plasma Cystatin C (CysC) for early detection of contrast-induced acute kidney injury (CIAKI) remains un-studied. We elucidated further on this issue. Methods: We searched PubMed, MEDLINE, and Embase from inception until March 2018 for studies evaluating diagnostic accuracy of CysC for detecting CIAKI in patients exposed to contrast agents during diagnostic examinations or cardiac/peripheral catheterizations. Results: A total of 10 relevant studies, comprising 2554 patients, were included and divided into the <24 -h and 24 -h groups based on CysC measuring timing ( i.e., hours after contrast agent exposure). Compared with creatinine, pooled diagnostic odds ratio of CysC for detecting CIAKI of the <24 -h and 24 -h groups was 7.59 (95 % confidence interval [CI]: 1.31–44.08) and 53.81 (95 % CI: 13.57–213.26). Pooled sensitivity of the <24 -h and 24 -h groups was 0.81 and 0.88. Pooled specificity of the <24 -h and 24 -h groups was 0.64 and 0.88, respectively. Area under the hierarchical summary receiver operating characteristic curve of the <24 -h and 24 -h groups was 0.75 and 0.93. Conclusions: Measuring CysC at 24 h after contrast agent exposure shows higher diagnostic accuracy for early detection of CIAKI than measuring CysC at <24 h after contrast agent exposure.